Role of Herbal Plants on Autophagy - Susanti Husen; Ronny Lesmana; Hanna Goenawan; Setiawan Setiawan (Universitas Padjadjaran, 2020)
Autophagy is a biomolecular system known to play an important role in cell growth, development as well as defense mechanisms, and is also a physiological approach towards homeostasis maintenance. This phenomenon is an intermediary pathway in the pathogenesis and therapy of various disease types, and is currently a new treatment route in the medical world. Hence, it is necessary to deeply understand the regulations, to prepare a treatment strategy in the future. Conversely, there is a high utilization of drugs, in line with the numerous disease cases in the community. Some limited chemical forms have large but necessary side effects, including anticancer agents. The high incidence of resistance and polypharmacy has been implicated in adverse drug interactions, and exorbitant costs, thus the initiative to return back to natural means. Furthermore, herbal medicines have been used in treatments for thousands of years, prior to the discovery of modern medicine. The various types previously studied have been highly beneficial in various disease cases. This review on researches within the last 5 years identified some herbal research articles in the aspect of autophagy, which was then summarized in a table form. Meanwhile, autophagy has been used for cancer therapy, and many plants have the potential to be therapeutic for various diseases through this pathway. Hence, improving related knowledge adds a new dimension to herbal medicine application in the pharmaceutical industry.Keywords: Autophagy, herbal, cancer, metabolic diseases, liver injury, neurological disorderPeran Berbagai Tanaman Herbal pada AutofagiAbstrakAutofagi adalah sistem biomolekuler sel yang berperan penting dalam pertumbuhan sel, perkembangan dan mekanisme pertahanan, dan merupakan sebuah cara fisiologis untuk mempertahankan homeostasis. Autofagi digunakan sebagai jalur perantara untuk patogenesis dan terapi berbagai jenis penyakit, dan saat ini autofagi telah menjadi jalan pengobatan baru di dunia medis sehingga regulasi jalur autofagi harus dipelajari lebih dalam untuk mempersiapkan strategi pengobatan di masa depan. Di sisi lain, tingginya pemanfaatan obat-obatan sejalan dengan banyaknya kasus penyakit yang muncul di masyarakat. Beberapa obat kimia memiliki efek samping yang besar tetapi jumlahnya terbatas, misalnya pada obat antikanker. Selain itu, tingginya kasus resistensi obat dan polifarmasi menyebabkan interaksi obat yang merugikan dan biaya obat yang tinggi. Oleh karena itu, pengobatan kini telah kembali ke alam. Herbal telah digunakan sebagai pengobatan selama ribuan tahun sebelum pengobatan modern ditemukan. Berbagai jenis herbal telah dipelajari dan memiliki manfaat yang baik dalam berbagai kasus penyakit di masyarakat. Pada artikel review ini, ditelaah artikel-artikel penelitian herbal yang mengambil jalur autofagi dan hasilnya dirangkum dalam bentuk tabel. Studi yang dilakukan dalam kurun waktu 5 tahun terakhir dimasukkan dalam review ini. Sampai sekarang, autofagi telah lebih banyak digunakan untuk terapi kanker dibandingkan yang tanpa kanker. Banyak tanaman herbal yang memiliki potensi untuk menjadi terapi berbagai jenis penyakit melalui jalur autofagi. Pengetahuan tentang autofagi menambah dimensi baru pada pengobatan herbal dan dapat diterapkan dalam industri farmasi.Kata kunci: Autofagi, gangguan metabolisme, gangguan saraf, herbal, kanker, kerusakan hati